Theoretical study of factors affecting ball velocity in instep soccer kicking - Ishii, H.; Yanagiya, T.; Naito, H.; Katamoto, S.; Maruyama, T. (Journal of Applied Biomechanics, 2012)
The objective of this study was to investigate the factors affecting ball velocity at the final instant of the impact phase (t1) in full instep soccer kicking. Five experienced male university soccer players performed maximal full instep kicks for various foot impact points using a one-step approach. The kicking motions were captured two dimensionally by a high-speed camera at 2,500 fps. The theoretical equation of the ball velocity at t1 given in the article was derived based on the impact dynamics theory. The validity of the theoretical equation was verified by comparing the theoretical relationship between the impact point and the ball velocity with the experimental one. Using this theoretical equation, the relationship between the impact point and the ball velocity was simulated. The simulation results indicated that the ball velocity is more strongly affected by the foot velocity at the initial instant of the impact phase than by other factors. The simulation results also indicated that decreasing the ankle joint reaction force during ball impact shifts the impact point that produces the greatest ball velocity to the toe side and decreasing the ankle joint torque during ball impact shifts the impact point that produces the greatest ball velocity to the ankle side.